Integrating knowledge, skills, and attitudes: professional training required for virtual reality therapists in palliative care - Woo, Olive K. L. (Frontiers in Medical Technology, 2023)
Fully immersive virtual reality (VR) is an advanced technology increasingly studied and used in palliative care for symptom management. While the findings shed a positive light on its therapeutic potential, VR carries adverse effects, leading to ethical concerns. Based on the clinical experiences of a registered clinical psychologist who is also a certified thanatologist, we put forward a perspective on the importance of professional training for VR therapists in view of the possible risks posed by VR in palliative care. We propose professional trainings on knowledge, skills, and attitude to ensure patients' safety while maximizing the therapeutic benefits of VR. Given the scarcity of reports on such an area, we hope this perspective article opens up discussions and contributes to current understanding and emerging future directions to ensure the quality and ethical delivery of VR in palliative care.